1990
DOI: 10.1073/pnas.87.15.5643
|View full text |Cite
|
Sign up to set email alerts
|

Folding and activity of hybrid sequence, disulfide-stabilized peptides.

Abstract: Peptides have been synthesized that have hybrid sequences, partially derived from the bee venom peptide apamin and partially from the S peptide of ribonuclease A. The hybrid peptides were demonstrated by NMR spectroscopy to fold, forming the same disulfides and basic three-dimensional structure as native apamin, containing a f-turn and an a-helix.These hybrids were active in complementing S protein, reactivating nuclease activity. In addition, the hybrid peptide was effective in inducing antibodies that cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…The linear least squares fit of the data from 2SOC to 7 5°C is also shown. The typeS of connectivities observed are exactly the same as those in both apamin (Pease & Wemmer, 1988) and the Apa-S hybrid (Pease, et al, 1990) for the first 16 residues at 0°C and 25°C. These include the aH-NH-NH-NH connectivity characteristic of the type I 13-turn, and i,i+2 connectivity at the beginning of the helix, and the continued NH-NH connectivities in the a-helix from residue 9 through residue 16.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…The linear least squares fit of the data from 2SOC to 7 5°C is also shown. The typeS of connectivities observed are exactly the same as those in both apamin (Pease & Wemmer, 1988) and the Apa-S hybrid (Pease, et al, 1990) for the first 16 residues at 0°C and 25°C. These include the aH-NH-NH-NH connectivity characteristic of the type I 13-turn, and i,i+2 connectivity at the beginning of the helix, and the continued NH-NH connectivities in the a-helix from residue 9 through residue 16.…”
supporting
confidence: 64%
“…It has been shown that a disulfide framework, taken from the bee venom peptide apamin, can be used to make hybrid sequence peptides with defmed conformations and high stability (Pease, et al, 1990). This chapter describes the application of.this approach to make a hybrid sequence peptide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2); the presence of a helical conformation is confirmed by the small values of 3 J HN-H␣ for these residues. The data for residues [17][18][19] are not indicative of a well formed helix, suggesting that they form a frayed terminus to the helix or adopt a turn conformation. These findings are in line with the structure modeled for APA14 and are consistent with the three-dimensional structures determined for other apamin peptides (35).…”
Section: Apamin Hybrid Peptide Structural Characterization-thementioning
confidence: 99%
“…These disulfides lock the COOH-terminal half of apamin (residues 9 -16) into a helical conformation (18,35). Various sequences can be substituted into the COOH terminus of apamin and forced into a helical conformation by the presence of these disulfide bridges (19). 1 The apamin framework can be used to present either the hydrophobic or hydrophilic face of an amphipathic helix (17), and thus it serves as a useful tool for examining the structural requirements for binding to cpn60.…”
mentioning
confidence: 99%